Benefit-risk assessment of sonidegib and vismodegib in the treatment of locally advanced basal cell carcinoma - Antonio J García Ruiz; Nuria García-Agua Soler; Enrique Herrera Acosta; Iris Zalaudek; Josep Malvehy (BioExcel Publishing Ltd, 2022)
Background: Sonidegib and vismodegib are Hedgehog pathway inhibitors (HhIs) that play a relevant role in the management of locally advanced basal cell carcinoma (laBCC). This study compared the efficacy and safety of both HhIs based on their available data using effect size measures such as number needed to treat (NNT), number needed to harm (NNH), and likelihood to be helped or harmed (LHH). Methods: We reviewed data from pivotal trials of sonidegib (BOLT) and vismodegib (ERIVANCE). The NNT for sonidegib and vismodegib was calculated from objective response rate (ORR) values. The NNH was calculated from data relating to treatment discontinuation due to adverse events (AEs) and incidence of AEs. The LHH was calculated as the ratio between the corresponding NNH and NNT. Results: For sonidegib (200 mg), the NNT for ORR at 18 months was 1.65 (95% CI 1.35-2.01) whilst that for vismodegib (150 mg) at 21 months was 2.10 (95% CI 1.65-2.82). The NNH related to treatment discontinuation due to AEs was 1.9 (95% CI 1.6-2.5) for sonidegib and 1.8 (95% CI 1.4-2.2) for vismodegib. The LHH for sonidegib and vismodegib related to treatment discontinuation due to AEs was 1.14 and 0.84, respectively, whilst the LHH according to AEs of grade ≥3 was 1.41 for sonidegib and 0.85 for vismodegib. Conclusions: Sonidegib showed a better benefit-risk ratio compared to vismodegib, being more likely to achieve therapeutic response than to AEs leading to discontinuation. These results should be confirmed in clinical practice and/or in a direct comparison study.